150 EDUCAŢIA TEHNOLOGICĂ: DILEME ŞI DESCHIDERI ACTUALE PRIVIND STRATEGIILE CENTRĂRII PE ELEV ÎN ÎNVĂŢĂMÂNTUL PREUNIVERSITAR ROMÂNESC - ANALIZA COMPARATIVĂ A PROGRAMELOR ŞCOLARE DIN ÎNVĂŢĂMÂNTUL OBLIGATORIU (domeniul pedagogie) - USM ADMIN (Moldova State University, 2007)
The comparative study of teaching programmes from the Romanian compulsory education for the objects in the curricular area "Technologies" can be approached in an original manner from the perspective of student centred strategies. At least three elements of novelty are brought together: reconsidering technological education as a formative process, from the perspective of its specificity, its role and importance within the educational system; seriously rethinking the manner in which programmes are worked out and their contents from a curricular point of view; their methodological restructuring, with a view to fully valuing the student as an important resource of the instructive-educational system. The study sprang from the intention of discovering whether these new programmes of a new educational approach meets with the student centred requirements. The answers shaped as conclusions will demonstrate that there are clearly such relations at the level of only one teaching programme, that is entrepreneurial education for the 10 th grade. At the level of other programmes, there are, however, numerous implicit openings and possibilities for developing the didactic strategy in the mentioned direction.